Primary pulmonary diffuse large B cell lymphoma presenting with features of organizing pneumonia: a case report - Sunjie Li; Yige Huang; Linlin Wang; Jintao Zhou (Journal of Medical Case Reports)
Abstract Background Primary pulmonary lymphoma is a rare subtype of non-Hodgkin lymphoma. Primary pulmonary diffuse large B cell lymphoma is an exceptionally rare form of primary pulmonary lymphoma. The clinical presentation of primary pulmonary diffuse large B cell lymphoma is often nonspecific, and imaging findings lack pathognomonic features, leading to frequent misdiagnosis and delayed treatment. Case presentation An 81-year-old Chinese man presented with a 4-month history of pulmonary nodules and a 2-month history of cough and dyspnea. Initial empiric antibiotic therapy for suspected lung infection was ineffective. A chest computed tomography scan revealed multiple patchy and nodular opacities in both lungs. Bronchoscopy ruled out bacterial and fungal infections, leading to a diagnosis of organizing pneumonia. Treatment with systemic corticosteroids provided transient symptomatic improvement, followed by clinical deterioration. Upon admission to hospital, a percutaneous lung biopsy confirmed the diagnosis of primary pulmonary diffuse large B cell lymphoma. The patient was transferred to the hematology department and received rituximab combined with reduced dose cyclophosphamide, doxorubicin, vincristine, and prednisolone chemotherapy. Despite treatment, the patient’s clinical condition deteriorated, leading to eventual mortality owing to disease progression. Conclusion Primary pulmonary diffuse large B cell lymphoma is a rare clinical condition with non-specific clinical manifestations, posing significant challenges for accurate and timely diagnosis. Early differentiation from other pulmonary conditions, such as organizing pneumonia, is critical to avoid delayed or inappropriate treatment, potentially improving patient outcomes. This case underscores the importance of a comprehensive diagnostic approach, including histopathological confirmation, in patients with pulmonary lesions that do not respond as expected to empiric therapies on the basis of preliminary diagnoses.